Picturing a gentleman dancing-master - Thorp, J (2012)
It was unusual for English dancing-masters, particularly during the first half of the eighteenth century, to be the subject of formal studio portraits, but one who was depicted in this way was Kellom Tomlinson. He has an important place in English dance history as a dance teacher and author of a finely illustrated dance manual, The Art of Dancing, first published in 1735 under the patronage of Catherine, 4th Viscountess Fauconberg; less well known however are his connections with a wider circle of wealthy catholic patrons whose families he taught. It has long been thought that the only surviving portrait of Tomlinson is the mezzotint of 1754 by François Morellon La Cave, and that the original portrait (by Richard Van Bleeck in 1716) from which it was copied, was lost. New evidence concerning the existence of that original portrait now provides a rare opportunity to compare the two images and consider what they tell us about the relationships between Tomlinson and his patrons and the development of his career.